Impact of neuraminidase inhibitor treatment on hospitalisation in patients with pandemic influenza: a multi-method modelling approach - Venkatesan, Sudhir (2019)
Background: Influenza pandemics are public health emergencies that can have potentially serious consequences. The 2009-10 influenza A(H1N1) pandemic was the first pandemic of the 21st century, and neuraminidase inhibitor (NAI) treatment was an important component of pandemic influenza mitigation plans around the world. While NAIs were licensed on the basis of reducing duration of illness in infected patients, their effectiveness in reducing complications, particularly in patients with pandemic influenza is less clear. Evaluating the impact of NAI treatment on outcomes of public health interest in patients with pandemic influenza is, therefore, crucial to informing future pandemic influenza preparedness plans. The main aim of this thesis was to evaluate the impact of NAI treatment on hospitalisation in patients with pandemic influenza.